Linking the local with the global: gender, childhoods, and development. (22nd January 2020) - Rothchild, Jennifer
In this paper, I advocate for reintroducing the gender and development (GAD) perspective, but this time with a twist: bringing the standpoints of children into the approach. This new version of the GAD approach would allow us to envision a nexus of gender, childhoods, and development. Specifically, life histories collected from youth living in children's homes in Nepal illuminate how particular populations carry the impact of development, globalisation, and human progress. Listening to the voices of youth at the local level provides us with a unique opportunity to envision the transformative potential at a much broader level.